REIMAGINING OF ANITA DIAMANT’S THE RED TENT INTO A REVISIONED FEMINIST HISTORY. (International Journal of Food and Nutritional Sciences, 2022)
Anita Diamant’s The Red Tent discusses the history of the Israelites from a different perspective. The author tells the story of the biblical character Dinah, Jacob’s daughter and Joseph’s sister, vizier of Israel according to the Hebrew Bible. In the Bible, Dinah’s story is mentioned briefly. Diamant tries to give a voice to the character of Dinah as well as her mothers. The novel The Red Tent is a path-breaking work and a landmark in the history of feminism. The Red Tent is a novel more sympathetic to female characters than male and the first half of the novel is pretty much all about the relationships between the women. One of the strongest themes in the novel is women’s relationships. The paper tries to bring how the author has tried to envision the biblical story of Dinah into feminist fiction.